HADITS DHA’IF DAN HUKUM MENGAMALKANNYA - Muhamad Halim Fatahillah; Rahmad Egi Cahyono; Salman Lokollo (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2024)
This study aims to analyze and review the use of dha’if (weak) hadith in Islamic law, considering the significant differences of opinion among scholars. Hadith is the second primary source of Islamic law after the Quran and plays a crucial role in explaining the Quran. However, dha’if hadith often becomes a subject of debate regarding its validity and application in Islamic jurisprudence. The majority of hadith scholars and jurists have differing views on the use of dha’if hadith, with some scholars completely prohibiting it and others allowing it under certain conditions.This research employs a qualitative approach with a descriptive-analytical method. Primary data includes dha’if hadiths found in major hadith collections, opinions of scholars on dha’if hadith, and statements from key figures in the fields of hadith and fiqh. Secondary data consists of supporting literature such as books, journals, scholarly articles, and writings of classical and contemporary scholars. Data collection techniques involve literature review and interviews with experts in hadith and fiqh.Data is analyzed using descriptive-analytical techniques, involving the categorization of hadith based on their degree of weakness, analysis of scholars' views on the use of dha’if hadith, and interpretation of data to construct a strong argument regarding the legal use of dha’if hadith. Data validation is conducted through source and method triangulation to ensure the accuracy and reliability of the research findings.